Data Mining Pubmed Identifies Core Signalings and miRNA Regulatory Module in Glioma - Kang, Chunsheng; Zhang, Junxia; Wang, Yingyi; Liu, Ning; Liu, Jilong; Zeng, Huazong; Jiang, Tao; You, Yongping; Pu, Peiyu (IntechOpen, 2011)
None